Fabrication of a Micro-Fluid Gathering Tool for the Gastrointestinal Juice Sampling Function of a Versatile Capsular Endoscope - Dong-il Dan Cho; Sangmin Lee; Kyo-in Koo (Sensors, 2011)
This paper presents a micro-fluid gathering tool for a versatile capsular endoscope that employs a solid chemical propellant, azobisisobutyronitrile (AIBN). The proposed tool consists of a micro-heater, an AIBN matrix, a Venturi tube, a reservoir, an inlet, and an outlet. The micro-heater heats the AIBN matrix to be decomposed into by-products and nitrogen gas. This nitrogen gas generates negative pressure passing through the Venturi tube. The generated negative pressure inhales a target fluid from around the inlet into the reservoir. All the parts are designed to be embedded inside a cylindrical shape with a diameter of 17 mm and a height of 2.3 mm in order to integrate it into a versatile developmental capsular endoscope without any scaledown. Two sets of the proposed tools are fabricated and tested: one is made of polydimethylsiloxane (PDMS) and the other is made of polymethylmethacrylate (PMMA). In performance comparisons, the PDMS gathering tool can withstand a stronger pulling force, and the PMMA gathering tool requires a less negative pressure for inhaling the same target fluid. Due to the instant and full activation of the thin AIBN matrix, both types of gathering tool show analogous performance in the sample gathering evaluation. The gathered volume is approximately 1.57 μL using approximately 25.4 μL of AIBN compound.